The Flouting of Grice’s Cooperative Principle by Native and Non-Native Speakers of English - Safitri, Riski; Faridi, Abdurrachman (English Education Journal, 2017)
The application of cooperative principle and repair strategies in talk showdemonstrates their essential function in language use. This research was intended to explain the flouting maximd of Grice’s Cooperative principle by native and non native speakers of English (guests) in Insight with Desi Anwar talk show, the differences between them in flouting the maxims, how the host of the talk show used repair strategies to overcome the guests who flout the maxims, reasons of using the strategies, and the contribution of the findings to the teaching English as a foreign language. This research used descriptive qualitative method. The findings showed that native and non-native speakers in the talk show flouted all the maxims. There were no significant differences between the performances of the native and non-native speakers in flouting the maxims. The differences only in terms of the frequency of flouting the maxims and the way they flouted the quality maxim. There were three types of repair strategies used by the host. The findings of this study can be considered as the contribution of the study to the teaching English as a foreign language sincethe awareness of cooperative principle is important and repair strategies should be reinforced for classroom interaction.